Penerapan Algoritma Fuzzy Logic Mamdani Pada Alat Pemarut Kelapa Otomatis Berbasis IoT - Asminah, Asminah; Aminah, Siti; Juanta, Riki (Jurnal Tika, 2023)
Indonesia is rich in natural resources, one of which is the coconut plant. The area of ​​South Sumatra is one of the areas with quite a lot of coconut plants, usually residents use preparations from coconut plants where the coconut is grated first. To get the result of grated coconut still using traditional methods. So far, the coconut grating process is done manually, the process of turning on the tool to operate still requires strong energy, because the process is pulling the rope as a starter, and the amount of grated coconut produced is still the size of a fist to provide the right amount of grated coconut so it is considered very good. not efficient. Therefore we need a tool that can provide information on the amount of grated coconut produced through Internet of Things (IoT) technology that can be controlled using a smartphone. In this study using the Rapid Application Development (RAD) method, there are three phases in RAD, namely requirement planning, design workshop, and implementation of the mamdani fuzzy logic algorithm. The results of this study are the application of the mamdani fuzzy logic algorithm to a coconut grater where the Thinger io platform displays the amount of grated coconut and the process of starting the coconut grater machine is automatic. From the results of processing the fuzzy set domain data, the weight of grated coconut of 100gr – 1500gr is in the low category, the weight of 1600gr – 3100gr is in the medium category, and the weight of 3200gr – 5000gr is in the high category. The implication function obtained a minimum weight of -0.4 and a maximum weight of 1.46 while for low prices it has an implication value of 0.5 and high prices 1. The composition of the rules obtains a value of -0.0145. and the defuzzification value (affirmation) of the fuzzy set domain is -22.132.